Time series of vertical flux of zooplankton fecal pellets on the continental shelf of the western Antarctic Peninsula - Gleiber, Miram R.; Steinberg, Deborah K.; Ducklow, Hugh W. (Marine Ecology Progress Series, 2012)
Zooplankton fecal pellet contribution to particulate organic carbon (POC) flux over the continental shelf of the western Antarctic Peninsula (WAP) was investigated to better understand the possible effects of changes in zooplankton community structure, due to climate change, on carbon export. Fecal pellets were collected at 170 m depth in a moored sediment trap from January 2004 to January 2009. Fecal pellet shape and size (i.e., carbon content) were quantified to assess flux of pellets from different zooplankton taxa and compared between seasons and years. Fecal pellet POC constituted the dominant proportion of total POC flux, with summer (November to April) pellet POC flux (67%) significantly higher than winter (May to October) pellet POC flux (34%), while phytodetritus or fecal 'fluff' constituted the remainder. Cylindrical euphausiid pellets contributed to a monthly mean of 72% of total fecal pellet flux; ovoid copepod and tabular salp pellets contributed significantly less (22 and 6%, respectively). Cylindrical and ovoid pellet export was significantly higher in summer, while 48% of tabular pellet flux occurred in winter. Tabular pellets had the highest carbon content (median = 1.03 mu gC pellet(-1), highest 134.9 mu gC pellet(-1)), followed by cylindrical (0.20 mu gC pellet(-1)) and ovoid (0.04 mu gC pellet(-1)) pellets. As krill fecal pellets are the dominant component of particle export in the WAP, we hypothesize that a decrease in krill and increase in salps in the region could alter the export of POC to the deep sea.